Neighbours in Death: General Wendjabaendjed and the Chief Steward of Amun Ankhefenmut A/B/C - Thijs , Ad (Antiguo Oriente, 2025)
This article investigates whether the theory, advocated by Jansen-Winkeln, that there was only one Chief Steward of Amun Ankhefenmut can be reconciled with the chronology proposed by the author in earlier articles and it tries to answer the question why this apparent son of Herihor ended up buried in the Tanite Tomb of Psusennes I (Tomb III). It also deals with the careers of the fourth, third and second prophets of Amun during the 21st Dynasty and tries to provide a relative date for the Procession of Sons of Herihor from the Temple of Khonsu. With the general Wendjabaendjed, both his links to the royal family and the date of his burial are discussed. His burial, next to that of Ankhefenmut, is used to demonstrate that, contrary to what has been suggested, Ankhefenmut cannot have been the intended successor of Amenemnisu. Finally, a tentative explanation is suggested for the succession of Amenemope by Osochor.